Public universities employees perception of electronic information sharing between universities and the Ministry of Higher Education and Scientific Research - Mohammed, Mohammed Abdulameer (2017)
Electronic information sharing benefits organizations and institutions in various aspects including increasing the level of information accuracy and timeliness, improving the accountability and decision making, and minimizing the cost of information management. There is a high degree of information sharing between Iraqi public universities and Ministry of Higher Education and Scientific Research (MOHESR), however, limited electronic information sharing exists between them, which brings difficulties and delay in making decisions. This limitation also creates challenges and barriers in supporting the decentralization principle taken by the public universities in universities’ governance. Thus, there is a need to conduct a study to identify the possible steps and strategies to increase electronic information sharing between the ministry and universities. The main objective of this study is to propose a model of electronic information sharing between Iraqi public universities and MOHESR. Social Exchange Theory, Critical Mass Theory and Transactive Memory System Theory have been used to solve the problem and achieve the objectives. Purposive sampling has been used and multiple linear regression analyses were applied for data analysis. A total of 660 questionnaires have been distributed in five universities in Iraq and the returned response was 274 (42%). From the 16 factors proposed, ten factors are found to be significance which are IT capability, information quality, compatibility, complexity, data warehouse, top management, policy/legal framework, interagency trust, upper level leadership and social network. Based on the results obtained, the study presents a model of electronic information sharing between public universities in Iraq and MOHESR. A comprehensive understanding of this model will contribute to the improvement of the planning and implementation of three dimensions; technological, organizational and environmental of the public universities in their way forward to improvise electronic information sharing in the future. According to the findings, it can be concluded that three dimensions and ten factors can essentially increase the electronic information sharing among public universities and MOHESR.